MAKE A MAS MAS TOURIST VILLAGE INDEPENDEN WITH ACCOUNTING EMKM APPLICATION - Lalu Takdir Jumaidi Jumaidi; Iman Waskito; Satarudin Satarudin; Bambang Bambang (https://jurnal.fe.unram.ac.id/index.php/abdimas/about/privacy, 2021)
Lunching on the establishing and developing “a thousand villages’ destinations” is possible due to the unique potential “resources”, such as local languages, literature opuses, traditional songs and dances, high value of handicrafts, certain unique and nature production modes, the available of beautiful unique cultures, challenging with its historical background, sacred places and identified with spirituality. These potencies can support the establishing and developing “a thousand villages’ destinations”. For the sake of practice on finding out and evaluating villages’ potencies which can be established to be villages’ destinations. The establishment and development made suite to stakeholders. Therefore, useful common accountant knowledge is going to be introduced in hope that it could be used to make standard report, control and make decision, and develop business. Despite promoting through global internet, the establishing and developing can also be done by having competition on destinations’ packet. It is made and suited with other destinations so that it could create more innovating and interesting products of destinations’ packet.